Editorial: Special Issue on Financial Planning - Mark Brimble; Brian Murphy; Rakesh Gupta (Australasian Accounting, Business and Finance Journal, 2012)
The special edition presents current research in the area of financial planning. With the continual upheaval in global financial markets (including Australia), the general trend towards self-funded retirement and less reliance on the state, financial crises and the continual regulatory changes in the financial markets, this issue is timely and topical. This is the third special edition on financial planning, providing an excellent outlet for quality research in financial planning.
Keywords: Editorial; Financial Planning